RNA-based mechanisms underlying axon guidance - Shigeoka, Toshiaki (The Rockefeller University Press, 2013)
Axon guidance plays a key role in establishing neuronal circuitry. The motile tips of growing axons, the growth cones, navigate by responding directionally to guidance cues that pattern the embryonic neural pathways via receptor-mediated signaling. Evidence in vitro in the last decade supports the notion that RNA-based mechanisms contribute to cue-directed steering during axon guidance. Different cues trigger translation of distinct subsets of mRNAs and localized translation provides precise spatiotemporal control over the growth cone proteome in response to localized receptor activation. Recent evidence has now demonstrated a role for localized translational control in axon guidance decisions in vivo.